(untitled) (Tribhuvan University Journal of Microbiology, 2025)
Objective: The objective of this study is to determine the prevalence of Extended-Spectrum β-Lactamase (ESBL) production and CTX-M genes among Klebsiella species isolated from clinical specimens. Methods: A total of 1,815 clinical samples—including urine, blood, sputum, pus, and body fluids were collected at Himal Hospital Kathmandu, during 2019–2020. Standard microbiological techniques were used for isolation and identification of bacterial pathogens. Antimicrobial susceptibility testing was performed using the modified Kirby–Bauer disk diffusion method following CLSI (2019) guidelines. ESBL screening was conducted using third-generation cephalosporins, and confirmation was done via the Double Disk Synergy Test (DDST). Molecular detection of the CTX-M gene was performed using PCR with specific primers targeting a 544 bp amplicon. Results: Among 1,815 clinical samples, urine constituted the majority (65.8%), followed by blood (25.1%). Escherichia coli was the predominant isolate (89.1%), while Klebsiella pneumoniae (6.2%) and Klebsiella oxytoca (0.74%) comprised a smaller proportion. Of the 28 Klebsiella spp. isolates, the highest antibiotic sensitivity was observed toward Amikacin (60.7%) and Meropenem (57.1%), whereas complete resistance to Amoxicillin (100%) and high resistance to Cefixime (89.3%) and Cefotaxime (75.0%) were recorded. ESBL screening identified 22 (78.6%) potential ESBL producers, of which 18 (64.3%) were confirmed phenotypically. PCR analysis revealed the CTX-M gene in 7 of the 18 ESBL-positive isolates, demonstrating a notable presence of CTX-M–mediated resistance among Klebsiella spp. Conclusion: The findings highlight a concerning prevalence of ESBL production and CTX-M genes in Klebsiella species in the study population, underscoring the need for continuous surveillance, rational antibiotic use, and strengthened antimicrobial stewardship programs to limit the spread of multidrug-resistant strains.